THE EFFECTIVENESS OF ARRANGEMENT MODERN STORES MINIMARKET POLICY - Maghfira, Vanessa Putri (Efficient: Indonesian Journal of Development Economics, 2019)
The purpose of this study is to find out effectiveness of policy Law No.1 of 2014 on the Arrangement of Modern Minimarket in Semarang City and to know the supporting factors and inhibiting factors of the policy. The research method used in this research is using descriptive method percentage. The result of the research shows that policy of Law No.1 of 2014 about setup of Modern Minimarket arrangement in Semarang City is not yet effective with target that has been set. Supporting factors in this policy is the minimarket workforce comes from the local orkforce and the distance between the minimarket and traditional market already 500m. while the inhibiting factor in this policy there are still many minimarkets operating that are not in accordance with the rules that have been set. Tujuan dari penelitian ini adalah untuk mengetahui efektivitas kebijakan UU No.1 tahun 2014 tentang Pengaturan Pasar Minimarket Modern di Kota Semarang dan untuk mengetahui faktor pendukung dan faktor penghambat kebijakan tersebut. Metode penelitian yang digunakan dalam penelitian ini adalah menggunakan metode deskriptif persentase. Hasil penelitian menunjukkan bahwa kebijakan UU No.1 tahun 2014 tentang pengaturan pengaturan Minimarket Modern di Kota Semarang belum efektif dengan target yang telah ditetapkan. Faktor pendukung dalam kebijakan ini adalah tenaga kerja minimarket berasal dari orkforce lokal dan jarak antara minimarket dan pasar tradisional sudah 500 m. sedangkan faktor penghambat dalam kebijakan ini masih ada banyak minimarket yang beroperasi yang tidak sesuai dengan aturan yang telah ditetapkan.